Quantifying early marine diagenesis in shallow-water carbonate sediments. (1st September 2018) - Ahm, Anne-Sofie C.; Bjerrum, Christian J.; Blättler, Clara L.; Swart, Peter K.; Higgins, John A.
Abstract: Shallow-water carbonate sediments constitute one of the most abundant and widely used archives of Earth's surface evolution. One of the main limitations of this archive is the susceptibility of the chemistry of carbonate sediments to post-depositional diagenesis. Here, we develop a numerical model of marine carbonate diagenesis that tracks the elemental and isotopic composition of calcium, magnesium, carbon, oxygen, and strontium, during dissolution of primary carbonates and re-precipitation of secondary carbonate minerals. The model is ground-truthed using measurements of geochemical proxies from sites on and adjacent to the Bahamas platform (Higgins et al., 2018) and authigenic carbonates in the organic-rich deep marine Monterey Formation (Blättler et al., 2015). Observations from these disparate sedimentological and diagenetic settings show broad covariation between bulk sediment calcium and magnesium isotopes that can be explained by varying the extent to which sediments undergo diagenesis in seawater-buffered or sediment-buffered conditions. Model results indicate that the covariation between calcium and magnesium isotopes can provide a semi-quantitative estimate of the extent and style (fluid-buffered vs. sediment-buffered) of early marine diagenesis. When applied to geochemical signatures in ancient carbonate rocks, the model can be used to quantify the impact of early marine diagenesis on other geochemical proxies of interest (e.g. carbon and oxygen isotopes). The increasing recognition of early marine diagenesis as an important phenomenon in shallow-water carbonate sediments makes this approach essential for developing accurate records of the chemical and climatic history of Earth from the chemical and isotopic composition of carbonate sediments.